Overview of Quarter Life Crisis in College Students in the Millennial Era - Jalal, Novitamaulidya (International Journal of Education, Vocational and Social Science, 2023)
The purpose of this paper is to find out the description of the quarter life crisis in students in the millennial era. This study uses a descriptive quantitative research method. The research subjects were students aged 18-22 years in Makassar who were willing to be research subjects. The research instrument was a questionnaire consisting of questions related to the quarter life crisis in college students. The data obtained was in the form of percentages. Based on the results of research conducted on 32 student subjects aged 18-25 years in Makassar who were willing to fill out a questionnaire, the data obtained consisted of 25% (8 people) male and 75% (24 people) female. There were 60% of subjects who thought that their new roles and tasks as adults were difficult to implement. There were 38% of subjects who felt that subjects were required by themselves and the environment to fulfill various new roles and tasks as early adults. When thinking about the future, most of the subjects, namely 59.5%, felt worried emotions, 68.75% people were worried about their financial condition or financial condition in the future, 25 were worried about their education and career, 31.25% were worried about building a family, and there are 59.5% of respondents who are still confused about their life goals. Thus, it is known that there are students in the digital era who are experiencing a quarter life crisis, especially in the aspect of worrying about their financial condition and future career. The implications of this research are expected to be useful for students, educators, and parents in understanding the condition of students in the current the millenial era in assessing their readiness for the future. Keywords: college students, the millennial era, quarter life crisis